PENGARUH VARIASI KADAR PEREKAT TAPIOKA TERHADAP KARAKTERISTIK BRIKET ARANG LIMBAH KAYU SENGON (Falcataria mollucana) - Siti Mutiara Ridjayanti; Wahyu Hidayat; Rahmi Adi Bazenet; Irwan Sukri Banuwa; Melya Riniarti (ULIN: Jurnal Hutan Tropis, 2022)
Biomass waste that has not been utilized properly is wood waste from Sengon (Falcataria moluccana). There is a high potential of these wastes to be used as solid fuel. The quality can be further improved by converting them into charcoal briquettes. This study aimed to determine the effects of adhesive content on the bioenergetic properties of charcoal briquette from Sengon wood wastes. The charcoal briquettes were produced by mixing charcoal powders with tapioca starch as an adhesive with a concentration of 5%, 10%, and 15%. Biomass briquette from Sengon wood particles (without pyrolysis) was also produced for comparison (control). The oven-dry density of briquettes of 0,23 – 0,25 g/cm3. Higher adhesive content increased the density of briquettes. The bioenergetic properties of the charcoal briquette were evaluated. The results showed that charcoal briquettes were more hydrophobic than biomass briquettes (control). The results of proximate analysis of charcoal briquettes showed volatile matter of 24,96–31,80%; ash content of 3,16–3,24%; and fixed carbon of 58,68–66.40%. Higher adhesive content increased the volatile matter, moisture content, and ash content of the charcoal briquettes and decreased the fixed carbon. The charcoal briquettes have a calorific value of 25,68-27,35 MJ/kg, which is remarkably higher than the control. Higher adhesive content tended to decrease the calorific value of the charcoal briquettes. Lower adhesive content will produce briquettes with good bioenergy characteristics. Sengon wood waste charcoal briquettes with 5% adhesive content has great potential to be developed as an alternative energy source.Keywords: Adhesive content, Charcoal briquettes, Pyrolysis, Sengon (Falcataria moluccana); Tapioca starch